Das neue Erdgaslager von Lacq und seine Bedeutung für die Energieversorgung in Frankreich - Hartke, Wolfgang (ERDKUNDE, 1958)
In 1953, near Lacq, 25 Km. north west of Pau, gas bearing strata were located in the crest of an anticline. The strata consist of upper Jurassic to lower Cretaceous rocks and the certain reserves are estimated to be at least 125 milliard cu.m. of gas. It is anticipated that by 1961 the daily production will be 10 million cu.m., an increase of one-third more than the sum total of the present output of all French gas works. It is furthermore expected to produce annually as by-products 150,000 tons of petrol and 600,000 tons of sulphur in addition to butane and propane. Already in 1957 the daily production rose to 1 million cu.m. gas. It is planned to construct an extensive network of pipelines to supply energy for the industries of Nantes, Limoges, Clermont-Ferrand, Vichy and St. Etienne in the west. Another main pipe is to lead eastwards via Toulouse to Montpellier, Avignon and Valance, to Lyons as well as to Marseilles and Toulon. It is expected that these developments will have repercussions on the present sources of energy; in particular the competitive position of the small coal fields of the central plateau, which now produce about 2.5 million tons per year, will be affected. Another probable consequence of an ample supply of energy in south-western France will be the emergence of industrial enterprises whose energy demands are particularly great like chemical industries, aluminium plants, cement works, thermo-electric power stations and others. It is furthermore likely that the social structure will undergo a change, especially in the rural areas, as particularly in this region there is a high proportion of family farms operating at a low degree of efficiency. Lastly the question of water supply for the industry, as well as that of the disposal of effluents, will pose difficult problems. Thus it is to be expected that the indirect consequences of the gas field on the geographical structure will be very much greater than those of oil.